Intrathecal Meperidine for Prevention of Shivering During Transurethral Resection of Prostate - Davoudi, Maryam; Mousavi-Bahar, Seyed Habib; Farhanchi, Afshin (Urology Journal, 2009)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!-- /* Font Definitions */ @font-face {font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:1; mso-generic-font-family:roman; mso-font-format:other; mso-font-pitch:variable; mso-font-signature:0 0 0 0 0 0;} @font-face {font-family:Tahoma; panose-1:2 11 6 4 3 5 4 4 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:1627400839 -2147483648 8 0 66047 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman";} p.CharCharCharChar, li.CharCharCharChar, div.CharCharCharChar {mso-style-name:" Char Char Char Char"; mso-style-unhide:no; margin-top:0cm; margin-right:0cm; margin-bottom:8.0pt; margin-left:0cm; line-height:12.0pt; mso-line-height-rule:exactly; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Tahoma","sans-serif"; mso-fareast-font-family:"Times New Roman"; mso-bidi-font-family:"Times New Roman";} .MsoChpDefault {mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt;} @page Section1 {size:612.0pt 792.0pt; margin:72.0pt 72.0pt 72.0pt 72.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]--> Introduction: The aim of this study was to investigate low-dose intrathecal meperidine for prevention or alleviation of shivering after induction of spinal anesthesia for transurethral resection of the prostate (TURP). Materials and Methods: In a randomized controlled trial, 80 patients scheduled for TURP under spinal anesthesia were assigned into two groups of case and control. Spinal anesthesia was performed using 75 mg of hyperbaric lidocaine 5% plus meperidine, 15 mg, in the patients of the case group and the same dose of lidocaine plus normal saline in the patients of the control group. Shivering episodes were recorded during the operation and in the recovery room. Data on systolic blood pressure, heart rate, arterial oxygen saturation, and body temperature were collected before the induction of anesthesia; 5, 15, and 30 minutes after the induction; and in the recovery room. Results: Maximum level of sensory block was similar in the patients of the case and control groups. Shivering was not seen in the patients who received meperidine, while in the control group, 11 (27.5%) experienced some degrees of shivering (P = .001). Blood pressure, body temperature, and arterial oxygen saturation did not have a clinically significant change and they were not different between the two groups. Side effects of opioids were unremarkable. Conclusion: Low-dose intrathecal meperidine is effective and safe in reducing the incidence of shivering associated with spinal anesthesia for TURP.